2015
DOI: 10.4025/actascianimsci.v37i3.26437
|View full text |Cite
|
Sign up to set email alerts
|

<b>Effect of feeding canola meal to laying Japanese quails

Abstract: This study evaluated the effect of different levels of canola meal in the diet to laying Japanese quails on productive performance, egg quality and economic viability. A total of 120 80-day-old Japanese quails (Coturnix coturnix japonica) with average weight 146.54 ± 12 g were evaluated during 84 days. Dietary treatments consisted of the replacement of soybean meal with canola meal at 0, 10, 20, 30, 40 or 50%. We evaluated economic viability, productive performance, internal and external quality of eggs. Data … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…More intensive coloration is advantageous from the producer’s point of view since it was shown that eggs with darker yolk colors are more readily chosen by consumers [ 37 ]. Our results are in line with those obtained by Moraes et al [ 10 ]; the increase in canola meal dose contributed to better (more intensive) yolk coloration. Moreover, in a study by Blair et al [ 26 ], the addition of rapeseed meals fed to Babcock hens tended to darken yolk.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…More intensive coloration is advantageous from the producer’s point of view since it was shown that eggs with darker yolk colors are more readily chosen by consumers [ 37 ]. Our results are in line with those obtained by Moraes et al [ 10 ]; the increase in canola meal dose contributed to better (more intensive) yolk coloration. Moreover, in a study by Blair et al [ 26 ], the addition of rapeseed meals fed to Babcock hens tended to darken yolk.…”
Section: Discussionsupporting
confidence: 93%
“…The higher proportion may cause deterioration of production efficiency (growth rate, laying production); however, the quality of obtained eggs, except the yolk color, did not depend on the experimental factor [ 9 ]. Similar observations were made by Moraes et al [ 10 ], however, using a considerably higher proportion of rapeseed meal (30%, 40% and 50% in relation to soybean meal).…”
Section: Introductionsupporting
confidence: 89%
“…However, the presence of anti-nutritional factors ( ANF ) such as fibre (12%) and glucosinolates (3.8 µmol/g) (Disetlhe et al, 2018 ) in CM could hinder growth by interfering with nutrient digestion and absorption (Wickramasuriya et al, 2015 ) as well as carcass composition and meat quality in indigenous chickens. Indeed, these ANFs have been reported to reduce growth performance in broilers (Payvastegan et al, 2017 ) and quails (Moraes et al, 2015 ). Glucosinolates interfere with thyroid hormone synthesis, causing liver damage and appetite depression (Tripathi and Mishra, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the use of canola meal in quail diets could allow versatility in feed formulation. Several studies have reported that the inclusion of canola meal up to 120 g/kg had no negative influence on feed utilisation, performance, and meat quality traits of the quail [ 16 , 58 ].…”
Section: Nutritional Strategies To Promote a Sustainable And Profitable Quail Businessmentioning
confidence: 99%